Dichotomous Distribution of Putative Cholinergic Interneurons in Mouse Accessory Olfactory Bulb - Marking, Sarah; Krosnowski, Kurt; Ogura, Tatsuya; Lin, Weihong (Frontiers in Neuroanatomy, 2017)
Sensory information processing in the olfactory bulb (OB) relies on diverse populations of bulbar interneurons. In rodents, the accessory OB (AOB) is divided into two bulbar regions, the anterior (aAOB) and posterior (pAOB), which differ substantially in their circuitry connections and associated behaviors. We previously identified and characterized a large number of morphologically diverse cholinergic interneurons in the main olfactory bulb (MOB) using transgenic mice to visualize the cell bodies of choline acetyltransferase (ChAT-expressing neurons and immunolabeling (Krosnowski et al., 2012). However, whether there are cholinergic neurons in the AOB is controversial and there is no detailed characterization of such neurons. Using the same line of ChAT(BAC)-eGFP transgenic mice, we investigated cholinergic neurons in the AOB. We found significant differences in the number and location of GFP-expressing (GFP+), putative cholinergic interneurons between the aAOB and pAOB. The highest numbers of GFP+ interneurons were found in the aAOB glomerular layer (aGL) and pAOB mitral/tufted cell layer (pMCL). We also noted a high density of GFP+ interneurons encircling the border region of the pMCL. Interestingly, a small subset of glomeruli in the middle of the GL receives strong MCL GFP+ nerve processes. These local putative cholinergic-innervated glomeruli are situated just outside the aGL, setting the boundary between the pGL and aGL. Many but not all GFP+ neurons in the AOB were weakly labeled with antibodies against ChAT and vesicular acetylcholine transporter (VAChT). We further determined if these GFP+ interneurons differ from other previously characterized interneuron populations in the AOB and found that AOB GFP+ interneurons express neither GABAergic nor dopaminergic markers and most also do not express the glutamatergic marker. Similar to the cholinergic interneurons of the MOB, some AOB GFP+ interneurons express the calcium binding protein, calbindin-D28K. Moreover, exposure to either a male intruder or soiled bedding from a mating cage leads to an increase in the number of c-Fos-expressing MCL GFP+ neurons. Taken together, our data reveal a population of largely unidentified putative cholinergic neurons in the AOB. Their dichotomous distribution in the aAOB and pAOB suggests region-specific cholinergic involvement in AOB olfactory information processing.